Equipping street-level bureaucrats with green skills for sustainable public policy change - Kesternich, Martin; Kiepe, Karina; Reimsbach, Daniel; Trang, Simon Thanh-Nam; Yang, Philip (npj Climate Action)
Abstract The shift to a low-carbon economy requires developing green skills across sectors. This paper builds on a recent Perspective 1 article examining how institutional regimes shape green skill formation. Drawing on the microfoundations of management research, we propose a micro-level perspective of public sector green skill formation, thereby emphasizing the role of street-level bureaucrats serving as public servants who directly engage with citizens in implementing public policies and outline a research agenda.

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Political embeddedness and firms’ choices of earnings management strategies in China - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin (Accounting & Finance)
Abstract We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms’ choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs’ total earnings management level is higher than that of non‐PCEs.
Keywords: Economics; Econometrics and Finance (miscellaneous); Finance; Accounting

Bringing Signaling Theory to Intermediated Voluntary Disclosure. Commentary on “Detecting False Accounts in Intermediated Voluntary Disclosure” by Patrick Callery and Jessica Perkins - Hahn, Rüdiger; Reimsbach, Daniel (Academy of Management Discoveries)

Legitimation Strategies as Valuable Signals in Nonfinancial Reporting? Effects on Investor Decision-Making - Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter; Feder, Madeleine; Weißenberger, Barbara E. (Business & Society)
Companies disclosing negative aspects in sustainability reports often employ legitimation strategies to present mishaps in a favorable light. In incentivized experiments, we find that nonprofessional investors divest from companies with a negative sustainability-related incident, and that symbolic legitimation (which only evasively explains a negative incident) is not a strong enough signal to counter this divestment behavior. Even substantial legitimation (which reports on measures and behavioral change) mitigates the divestment decisions only if the company reports on concrete remediation actions in morally charged situations, such as social or environmental incidents. We elaborate these results in light of signaling and screening theory, and suggest the conceptual extension of “costly signals” to what we call “valuable signals.” We argue that valuable signals need be not only costly for the sender from an economic perspective but also perceived as appropriate by the receiver from a noneconomic perspective.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

Corporate governance and sustainable business conduct—Effects of board monitoring effectiveness and stakeholder engagement on corporate sustainability performance and disclosure choices - Manning, Bart; Braam, Geert; Reimsbach, Daniel (Corporate Social Responsibility and Environmental Management)
Abstract This study posits that, in the absence of extensive mandatory regulation and auditing, differences in internal and external corporate governance (CG) mechanisms will explain variations in choices concerning corporate sustainability reporting and the interrelated and underlying corporate sustainability performance (CSP). Specifically, we explore whether board monitoring effectiveness as a major internal CG mechanism and stakeholder engagement as a key external CG mechanism are positively associated with sustainability reporting quality (SRQ), compliance with generally accepted sustainability reporting standards (SRC) and guidelines, and CSP for a sample of Dutch firms that have voluntarily disclosed sustainability reports during the years 2012–2016. In addition to these direct effects, we also investigate the potential indirect effects of the CG mechanisms on SRQ and SRC via CSP and distinguish between nonlagged and lag effects. Using structural equation modeling, our results show that, in the short term, monitoring effectiveness positively affects SRQ and SRC. Stakeholder engagement positively affects SRQ and SRC in the short term and is positively related to SRQ via CSP in the longer term, indicating that active stakeholders, over time, may drive companies toward more sustainable business conduct. Finally, the findings that CSP is positively related to SRQ but negatively related to SRC provide further support for signaling and legitimacy theory, respectively. Companies with superior CSP disclose high‐quality information on CSP to signal the firm's superior sustainability performance, whereas poor performing companies legitimize their inferior CSP by complying with more reporting standards, rather than by directly improving their underlying CSP.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Development

Corporate governance and sustainable business conduct—Effects of board monitoring effectiveness and stakeholder engagement on corporate sustainability performance and disclosure choices - Manning, Bart; Braam, Geert; Reimsbach, Daniel (Corporate Social Responsibility and Environmental Management)
Abstract This study posits that, in the absence of extensive mandatory regulation and auditing, differences in internal and external corporate governance (CG) mechanisms will explain variations in choices concerning corporate sustainability reporting and the interrelated and underlying corporate sustainability performance (CSP). Specifically, we explore whether board monitoring effectiveness as a major internal CG mechanism and stakeholder engagement as a key external CG mechanism are positively associated with sustainability reporting quality (SRQ), compliance with generally accepted sustainability reporting standards (SRC) and guidelines, and CSP for a sample of Dutch firms that have voluntarily disclosed sustainability reports during the years 2012–2016. In addition to these direct effects, we also investigate the potential indirect effects of the CG mechanisms on SRQ and SRC via CSP and distinguish between nonlagged and lag effects. Using structural equation modeling, our results show that, in the short term, monitoring effectiveness positively affects SRQ and SRC. Stakeholder engagement positively affects SRQ and SRC in the short term and is positively related to SRQ via CSP in the longer term, indicating that active stakeholders, over time, may drive companies toward more sustainable business conduct. Finally, the findings that CSP is positively related to SRQ but negatively related to SRC provide further support for signaling and legitimacy theory, respectively. Companies with superior CSP disclose high‐quality information on CSP to signal the firm's superior sustainability performance, whereas poor performing companies legitimize their inferior CSP by complying with more reporting standards, rather than by directly improving their underlying CSP.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Development

Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance? - Wang, Zhi; Reimsbach, Daniel; Braam, Geert (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Integrated Reporting and Assurance of Sustainability Information: An Experimental Study on Professional Investors’ Information Processing - Reimsbach, Daniel; Hahn, Rüdiger; Gürtürk, Anil (European Accounting Review)
Keywords: Business; Management and Accounting (miscellaneous); Accounting; Business and International Management; Economics; Econometrics and Finance (miscellaneous); Economics and Econometrics; Finance

Tackling Complexity in Business and Society Research: The Methodological and Thematic Potential of Factorial Surveys - Oll, Josua; Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter (Business & Society)
Factorial surveys (FSs) integrate elements of survey research and classical experiments. Using a large number of respondents in a controlled setting, FSs approximate complex and realistic judgment situations through so-called vignettes—that is, carefully designed descriptions of hypothetical people, social situations, or scenarios. Despite being rooted, and predominantly applied, in sociology, FSs are particularly promising for business and society (B&S) scholars. Given the multiplicity, inherent complexity, and sometimes fuzziness of B&S research objects, conventional research methods inevitably reach their limits. This article, therefore, systematically presents methodological and thematic opportunities for FS studies in B&S research. It is argued that FSs are well suited to dealing with the complex interplay of societal-, organizational-, and individual-level factors in B&S research and to studying the principles underlying human perceptions, attitudes, values, social norms, and (anticipated) behavior. The application of the FS method is illustrated based on a showcase example in the realm of socially responsible investments (SRIs). As the literature on the conceptualization of FSs is limited, methodological challenges are addressed to guide B&S researchers past the common methodological pitfalls.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

Testing vs. building accounting theory with experimental research: insights from management research - Reimsbach, Daniel; Hauschild, Bastian (International Journal of Behavioural Accounting and Finance)
Keywords: Geology; Ocean Engineering; Water Science and Technology

Are we on track with sustainability literacy? - Hahn, Rüdiger; Reimsbach, Daniel (Journal of Global Responsibility)
Purpose – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the “Accounting View” and the “Sustainability View”, the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with “pure” accounting knowledge seemed more willing to simply accept the information. Practical implications – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an “add-on” to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.
Keywords: Business and International Management

Modeling sequential R&D investments: a binomial compound option approach - Hauschild, Bastian; Reimsbach, Daniel (Business Research)
Abstract In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management.
Keywords: Business; Management and Accounting (miscellaneous)

Pro forma earnings disclosure: the effects of non-GAAP earnings and earnings-before on investors’ information processing - Reimsbach, Daniel (Journal of Business Economics)
Keywords: Economics and Econometrics; Business and International Management

The Effects of Negative Incidents in Sustainability Reporting on Investors’ Judgments–an Experimental Study of Third‐party Versus Self‐disclosure in the Realm of Sustainable Development - Reimsbach, Daniel; Hahn, Rüdiger (Business Strategy and the Environment)
ABSTRACT This study examines how the disclosure of negative sustainability‐related incidents affects the investment‐related judgments of decision‐makers. Participants in a sequential 2 × 2 between‐subjects experiment first received a company's financial information before viewing additional sustainability information (by the company and by a non‐governmental organization (NGO); with and without negative disclosure). Results indicate that self‐reporting of negative incidents does not affect decision‐makers’ stock price estimates and investment decisions compared with judgments based on financial information only. However, third‐party disclosure of these incidents by a NGO has a negative affect on these investment‐related judgments. Furthermore, the magnitude of the NGO reporting effect depends on whether the company itself simultaneously reports these incidents. Thus, disclosing negative incidents in sustainability reporting could lose some of its apparent stigma. Instead of avoiding negative reporting altogether, managers might use it as a risk mitigation tool in their reporting strategy. The results also emphasize the power of the often‐mentioned ‘watchdog’ function of NGOs acting as stakeholder advocates. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management